Waterfall Method In Designing A Web-Based Waste Payment Information System (Case Study: Calincing Bukit Valley Housing Rt04/Rw008) - Agus Heri Yunial (LPPM Politeknik Aceh Selatan, 2024)
Valley Bukit Calincing Housing Exchange RT. 04 RW. 08 Bogor City is a housing complex that requires every resident to pay monthly waste fees. Payment of waste fees is payment of waste fees made by the treasurer who visits residents' homes to collect by giving a payment card to each resident and recording it again in the ledger. For reports, we still use Microsoft Excel. Because payment recording still uses Microsoft Excel, files on the laptop or PC can be lost or even accidentally deleted. Meanwhile, if it is recorded in a book, the book could be damaged/lost. The method that will be applied for this research is using Waterfall which has sequential stages starting from analysis, design, coding, testing and supporting stages, but in this research it only reaches the testing stage. Meanwhile, for the system development method using the OOAD method, a web-based application was created which is the right choice to simplify the treasurer's work in managing and managing waste fee payments. With this system, it can make it easier for residents to pay waste fees on time and reduce residents who like to pay past due dates because they are always reminded via email notifications sent by the treasurer so that the treasurer does not need to come to residents' homes to collect the waste fees. And with this waste fee payment information system, it makes it easier to manage the treasurer's waste fee payment reports.